IMPLEMENTASI HUKUM ISLAM TERHADAP PEMBAGIAN HARTA WARIS ANAK LUAR NIKAH (STUDI ANALISIS PUTUSAN MK NO.46/PUU-VIII/2010) - Laila, Maya; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The status of a child is closely related to whether or not a marriage is valid. As a result of a valid marriage, it will ensure that the status of the child is clear. Conversely, the result of an invalid marriage or not being registered at the KUA, will have implications for the unclear status of the child in a formal legal manner so that the child is considered an extramarital child. The issue was outlined in Constitutional Court Decision No.46/PUU-VIII/2010. However, the decision has generated a lot of controversy. Many people argue that the decision is the same as legalizing adultery in Indonesia, even contrary to Islamic law. Therefore, the purpose of this paper is to examine the issue of the implications of Constitutional Court Decision No.46/PUU-VIII/2010 on extramarital children. This research uses literature and normative law research methods. The research design uses an analytical study of Islamic law and Constitutional Court Decision No.46/PUU-VIII/2010. Data collection techniques are obtained from researching several books and intellectual works of scientists and/or scholars that are relevant and can be used as literature. Data analysis used descriptive qualitative, content analysis, and triangulation techniques. The results of this study state that the Constitutional Court's decision does not actually have legal implications for all children out of wedlock. Furthermore, this decision only has implications for children from siri marriage, but not children from adultery. Because it has been explained in the decision that to recognize a child out of wedlock, the father must be able to prove that he is really the biological father not only through science and technology, but also with other tools that can corroborate, for example, such as the marriage certificate of the father and mother which proves that they are really husband and wife who have entered into a legal marriage even though it is only limited to religion.